2018
DOI: 10.3389/fphar.2018.01257
|View full text |Cite
|
Sign up to set email alerts
|

Black Truffle Aqueous Extract Attenuates Oxidative Stress and Inflammation in STZ-Induced Hyperglycemic Rats via Nrf2 and NF-κB Pathways

Abstract: Background and Purpose: Tuber melanosporum (black truffle) has been considered as a medicinal mushroom for a long time. T. melanosporum has the ability to attenuate oxidative stress and in turn diabetes mellitus (DM). DM has become an awfully common chronic unwellness, threatening people’s well-being. There are nearly 1 in 10 people in the world affected by diabetes. Oxidative stress plays a crucial role in vascular complications related to DM. Our study aimed to attain an effective treatment method to allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…However, the antioxidant agents derived from dietary sources are promising elements to scavenge cell generating free radicals and protects β -cells. These antioxidant agents generally augment cellular antioxidant enzymes and inhibit β -cell apoptosis, which has been demonstrated to improve β -cell dysfunction and protect β -cells against glucotoxicity in diabetic animal models [5,94,95].…”
Section: Mechanism Of Dietary Polysaccharides On Anti-diabetic Actmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the antioxidant agents derived from dietary sources are promising elements to scavenge cell generating free radicals and protects β -cells. These antioxidant agents generally augment cellular antioxidant enzymes and inhibit β -cell apoptosis, which has been demonstrated to improve β -cell dysfunction and protect β -cells against glucotoxicity in diabetic animal models [5,94,95].…”
Section: Mechanism Of Dietary Polysaccharides On Anti-diabetic Actmentioning
confidence: 99%
“…In general, oxidative stress is connected with chronic inflammation in T2DM. During inflammation, several pro-inflammatory cytokines, namely, interleukin (IL)-1, IL-6, IL-8, IL-12, IL-18, interferon gamma (IF-γ), and tumor necrosis factor alpha (TNF-α), serve key functions in the dysfunction of islet cells and insulin receptors in the pancreas and eventually β -cell death [3,4,95,121]. Studies have shown that treatment using anti-inflammatory agents, including IL-1 and receptor antagonists, normalize glucose in the blood, improve insulin secretion, and decrease inflammation causing islet fibrosis.…”
Section: Mechanism Of Dietary Polysaccharides On Anti-diabetic Actmentioning
confidence: 99%
“…These ethnopharmacological techniques have been reinforced to yield bioactive compounds that support to improve modern medicine as beneficial tools [67][68][69][70]. Bioactive compounds often contribute a noteworthy function in drug finding by helping as a novel drug of interest and templates for synthetic agents [71][72][73]. Copious investigations have established that natural bioactive compounds have possible antimycobacterial activities [2,60,74,75].…”
Section: Challenges In Diagnosing and Treatment Of Ntm Diseasesmentioning
confidence: 99%
“…(black truffle), demonstrating decreased oxidative stress and inflammation in the liver. This effect was paralleled by an improvement of the total antioxidant capacity (T-OAC), CAT and SOD activity and vitamin C and E content in liver, which is comparable to the level of the positive control, treated with glibenclamide, a drug prescribed for T2DM (Table 1) [243,255].…”
Section: Antioxidative Effects Of Mushrooms In Livermentioning
confidence: 97%